AESTHETIC PERFORMANCE OF DIFFERENT WOOD SPECIES – VISUAL INTERACTION OF HUMAN BEING AND WOOD(BY ANALYZING THE COLOUR AND THE TEXTURE OF WOOD SEPARATELY) (Innovation in Woodworking Industry and Engineering design, 2026)
The paper deals with the issue of the visual performance of wood – the interaction of a human being and the visual perception of a wood surface. In order to analyze the human approach to a wood surface a new test method was developed. We assessed the impression of a wooden surface to test persons in two independent steps. One approach was the evaluation of a sample of pure wood-based colours without any texture. The second step was the evaluation of various wood textures by showing black & white photos of wood textures. The following wood species were tested: spruce, beech and ash, whereas the preferences of separated colour (wood colour tone without texture) were also investigated for maple and walnut in order to analyse the preferences for light/medium/dark tones of wood. As a general hypothesis we stated that the pure wood colour without any texture does not get the utmost appreciation by human beings, but superposing wood colour and wood texture exhibits the unique and deli-cate appearance of wood which is widely appreciated. In our study we could prove this hypothesis to a high extent.